Wave-absorbing honeycomb material and preparation method thereof
By stacking and laying the foam absorbing layer, transition layer and matching layer on the aramid paper honeycomb substrate, the problems of large thickness and poor wide frequency absorption effect of existing wave absorbing honeycomb materials are solved, and the effect of wide frequency absorption at a thinner thickness is achieved.
Patent Information
- Application Number
- CN202311109237.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-28
AI Technical Summary
The existing wave absorbing honeycomb materials have large thickness and poor wide frequency absorption effect, making it difficult to achieve wide frequency absorption at a thinner thickness.
The foam absorption layer, an optional foam transition layer and a foam matching layer are arranged in sequence on the aramid paper honeycomb substrate. By adjusting the dielectric constant and thickness of each layer, the effective absorption of electromagnetic waves in different frequency bands is achieved.
While reducing the thickness, the absorption bandwidth is effectively expanded, the electromagnetic wave absorption performance of wave absorbing different frequency bands is achieved, and the electromagnetic wave absorption performance of wave absorbing honeycomb materials is improved.
Smart Images

Figure CN119526833A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic wave absorbing materials, and in particular to a wave absorbing honeycomb material and a preparation method thereof. Background Art
[0002] The electromagnetic radiation and interference problems generated by electronic and electrical equipment during operation also restrict people's production and life, resulting in increasingly serious electromagnetic pollution in human living space. Electromagnetic pollution has become the fourth largest pollution after noise pollution, water pollution and air pollution. In order to effectively reduce the harm caused by electromagnetic wave radiation, on the one hand, the design of electromagnetic wave equipment can be optimized, and on the other hand, electromagnetic protection materials can be used to absorb and protect electromagnetic waves, and the latter is more effective in actual operation. Absorbing materials have received widespread attention as the core technology of aircraft stealth. Aramid paper honeycomb absorbing materials are widely used in aviation absorbing composite material structures due to their light weight, high strength and excellent absorbing effect. Traditional aramid paper honeycomb absorbing materials are obtained by impregnating absorbing slurry on the surface of aramid paper honeycomb and then curing it through surface drying (for example, see patent application CN115296039A). Traditional uniform absorbing honeycombs are difficult to take into account the effective absorption of low-frequency, medium-frequency and high-frequency electromagnetic waves due to the uniform distribution of absorbing agents on the side walls of the honeycomb, and it is difficult to achieve broadband absorption effects. In order to achieve good absorption effect in a wider frequency band, the absorbing honeycomb prepared by this method usually needs to be thicker, generally more than 40 mm, which limits its application in some special areas of the aircraft.
[0003] In view of the above problems, it is necessary to develop an absorbing honeycomb material and a preparation method thereof that can effectively expand the absorption bandwidth while reducing the thickness. Summary of the invention
[0004] The main purpose of the present invention is to provide a wave-absorbing honeycomb material and a preparation method thereof, so as to solve the problems of the existing wave-absorbing honeycomb materials, such as large wave-absorbing honeycomb thickness and poor broadband absorption effect.
[0005] In order to achieve the above-mentioned objectives, the present invention provides, on the one hand, an absorbing honeycomb material, comprising an aramid paper honeycomb substrate and a foam absorption layer, an optional foam transition layer and a foam matching layer stacked in sequence from the inside to the outside on the aramid paper honeycomb substrate, wherein the dielectric constant of the foam matching layer>the dielectric constant of the foam transition layer>the dielectric constant of the foam absorption layer.
[0006] Furthermore, the raw materials for forming the foam absorption layer include a first expandable phenolic resin, a first foaming agent, a first surfactant, a first curing agent and a first resistive absorbent, and the first resistive absorbent includes carbon black, graphene or nano nickel powder; preferably, the average particle size of the carbon black is 10 to 20 μm, and the resistivity is 0.5 to 1 Ω·cm; the specific surface area of the graphene is 1800 to 2000 m 2 / g, tap density is 0.08~0.1g / cm 3 The average particle size of nano nickel powder is 50-70nm.
[0007] Furthermore, by weight, the raw materials for forming the foam absorption layer include 200-210 parts of a first expandable phenolic resin, 8-9 parts of a first foaming agent, 4-4.5 parts of a first surfactant, 10-11 parts of a first curing agent, and 20-30 parts of carbon black, 5-6 parts of graphene or 100-120 parts of nano nickel powder.
[0008] Furthermore, the raw materials for forming the foam matching layer include a second expandable phenolic resin, a second foaming agent, a second surfactant, a second curing agent, hollow glass microspheres and a second resistive absorber, wherein the second resistive absorber includes carbon black and fumed silica; preferably, the average particle size of the hollow glass microspheres is 45 to 60 μm, and the bulk density is 0.29 to 0.35 g / cm 3 The average particle size of carbon black is 10-20 μm, the resistivity is 0.5-1 Ω·cm, and the specific surface area of fumed silica is 180-200 m 2 / g.
[0009] Further, the raw materials for forming the foam matching layer include, by weight, 200-210 parts of a second expandable phenolic resin, 8-9 parts of a second foaming agent, 4-4.5 parts of a second surfactant, 10-11 parts of a second curing agent, 20-30 parts of hollow glass microspheres, 4-5 parts of carbon black and 0.5-0.7 parts of fumed silica.
[0010] Furthermore, the raw materials for forming the foam transition layer include a third expandable phenolic resin, a third foaming agent, a third surfactant, a third curing agent and carbon black; preferably, the average particle size of the carbon black is 10 to 20 μm, and the resistivity is 0.5 to 1 Ω·cm.
[0011] Furthermore, the raw materials for forming the foam transition layer include, by weight, 200-210 parts of a third expandable phenolic resin, 8-9 parts of a third foaming agent, 4-4.5 parts of a third surfactant, 10-11 parts of a third curing agent and 4-5 parts of carbon black.
[0012] Furthermore, the thicknesses of the foam absorption layer, the foam matching layer and the foam transition layer are in the ranges of 3-4mm, 6-7mm and 3-4mm respectively; the dielectric constants of the foam absorption layer, the foam matching layer and the foam transition layer are in the ranges of 30-35F / m, 3-3.5F / m and 12-14F / m respectively.
[0013] Furthermore, the specification of the honeycomb holes of the aramid paper honeycomb matrix is a regular hexagon with a side length of 2.0 mm.
[0014] In order to achieve the above-mentioned purpose, another aspect of the present invention also provides a method for preparing the above-mentioned absorbing honeycomb material, comprising the following steps: 1) mixing the raw materials for forming the foam absorption layer, the foam matching layer and the optional foam transition layer to obtain the absorption layer rubber, the matching layer rubber and the optional transition layer rubber; 2) stacking the absorption layer rubber, the optional transition layer rubber and the matching layer rubber in sequence and arranging them on the aramid paper honeycomb substrate; 3) performing insulation after each arrangement to obtain the foam absorption layer, the foam matching layer and the optional foam transition layer respectively.
[0015] By applying the technical solution of the present invention, gradient foaming design is performed in the honeycomb holes, and the absorption bandwidth can be effectively expanded while reducing the thickness. The absorbing honeycomb prepared by the present invention comprises an aramid paper honeycomb matrix, a foam absorption layer and a foam matching layer. By adjusting the dielectric constant and thickness of the absorption layer and the matching layer, effective absorption of electromagnetic waves in different frequency bands can be achieved. The matching layer is composed of a foam material with a smaller dielectric constant, which can reduce the reflection of electromagnetic waves on the surface of the absorbing material. The foam absorption layer is composed of a material with a larger dielectric constant, which can fully absorb the electromagnetic waves transmitted from the matching layer. At the same time, the porous structure of the foam can further reflect and absorb the incident electromagnetic waves multiple times, enriching the loss path, so that broadband absorption can be achieved at a thinner thickness. By performing impedance matching design in the honeycomb holes, due to the presence of the matching layer, the reflection of the incident electromagnetic wave on the material surface is reduced compared to the traditional uniform absorbing honeycomb, so that more electromagnetic waves enter the material through the matching layer and are attenuated by the absorption layer. At the same time, on the basis of impedance matching, a foam porous structure is introduced to increase the transmission path and multiple reflections of the electromagnetic wave inside the material, further attenuate the incident electromagnetic wave, and broaden the effective absorption intensity and bandwidth. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1 The present invention provides a technical roadmap for the preparation method of the wave-absorbing honeycomb material. DETAILED DESCRIPTION
[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0019] As described in the background technology, the existing absorbing honeycomb materials have the problems of large thickness of absorbing honeycombs and poor broadband absorption effect. In order to solve the above technical problems, the present application provides an absorbing honeycomb material, comprising an aramid paper honeycomb substrate and a foam absorbing layer, an optional foam transition layer and a foam matching layer stacked and arranged from the inside to the outside on the aramid paper honeycomb substrate, wherein the dielectric constant of the foam matching layer is greater than the dielectric constant of the foam transition layer and the dielectric constant of the foam absorbing layer.
[0020] The absorbing honeycomb prepared by the present invention comprises an aramid paper honeycomb matrix, a foam absorbing layer, a foam matching layer and an optional foam transition layer. By adjusting the dielectric constant and thickness of the absorbing layer and the matching layer, effective absorption of electromagnetic waves of different frequency bands can be achieved. The matching layer is composed of a foam material with a relatively small dielectric constant, which can reduce the reflection of electromagnetic waves on the surface of the absorbing material. The foam absorbing layer is composed of a material with a relatively large dielectric constant, which can fully absorb the electromagnetic waves transmitted through the matching layer. At the same time, the porous structure of the foam can further reflect and absorb the incident electromagnetic waves multiple times, enriching the loss path, so that broadband absorption can be achieved at a relatively thin thickness. By performing impedance matching design in the honeycomb hole, due to the presence of the matching layer, the reflection of the incident electromagnetic wave on the surface of the material is reduced compared with the traditional uniform absorbing honeycomb, so that more electromagnetic waves enter the material through the matching layer and are attenuated by the absorption layer loss. At the same time, the foam porous structure is introduced on the basis of impedance matching, which increases the transmission path and multiple reflections of the electromagnetic wave inside the material, further attenuates the incident electromagnetic wave, and broadens the effective absorbing intensity and bandwidth.
[0021] In a preferred embodiment, the raw materials for forming the foam absorption layer include a first expandable phenolic resin, a first foaming agent, a first surfactant, a first curing agent and a first resistive absorbent, and the first resistive absorbent includes carbon black, graphene or nano nickel powder;
[0022] Preferably, the average particle size of the carbon black is 10 to 20 μm, and the resistivity is 0.5 to 1 Ω·cm; the specific surface area of the graphene is 1800 to 2000 m 2 / g, tap density is 0.08~0.1g / cm 3 The average particle size of the nano nickel powder is 50 to 70 nm.
[0023] In a preferred embodiment, the raw materials for forming the foam matching layer include a second expandable phenolic resin, a second foaming agent, a second surfactant, a second curing agent, hollow glass microspheres, and a second resistive absorber, wherein the second resistive absorber includes carbon black and fumed silica;
[0024] Preferably, the average particle size of the hollow glass microspheres is 45-60 μm, and the bulk density is 0.29-0.35 g / cm 3 The average particle size of the carbon black is 10 to 20 μm, the resistivity is 0.5 to 1 Ω·cm, and the specific surface area of the fumed silica is 180 to 200 m 2 / g.
[0025] In a preferred embodiment, the raw materials for forming the foam transition layer include a third expandable phenolic resin, a third foaming agent, a third surfactant, a third curing agent and carbon black;
[0026] Preferably, the average particle size of carbon black is 10 to 20 μm, and the resistivity is 0.5 to 1 Ω·cm.
[0027] In a preferred embodiment, the foaming agent is a plastic microsphere foaming agent, the foaming temperature is lower than the curing temperature, the curing agent is a mixture of one or both of benzoic acid and p-toluenesulfonic acid, and the surfactant is a mixture of one or both of Tween-10 and Tween-80.
[0028] As described above, by selecting specific components of the foam absorbing layer, the optional foam transition layer and the foam matching layer so that the dielectric constant of the foam matching layer is greater than the dielectric constant of the foam transition layer and greater than the dielectric constant of the foam absorbing layer, the electromagnetic wave absorption performance of the absorbing honeycomb material is improved.
[0029] In a preferred embodiment, the raw materials for forming the foam absorption layer include, by weight, 200-210 parts of a first expandable phenolic resin, 8-9 parts of a first foaming agent, 4-4.5 parts of a first surfactant, 10-11 parts of a first curing agent, and 20-30 parts of carbon black, 5-6 parts of graphene or 100-120 parts of nano nickel powder.
[0030] In a preferred embodiment, the raw materials for forming the foam matching layer include, by weight, 200-210 parts of a second expandable phenolic resin, 8-9 parts of a second foaming agent, 4-4.5 parts of a second surfactant, 10-11 parts of a second curing agent, 20-30 parts of hollow glass microspheres, 4-5 parts of carbon black and 0.5-0.7 parts of fumed silica.
[0031] In a preferred embodiment, the raw materials for forming the foam transition layer include, by weight, 200-210 parts of a third expandable phenolic resin, 8-9 parts of a third foaming agent, 4-4.5 parts of a third surfactant, 10-11 parts of a third curing agent and 4-5 parts of carbon black.
[0032] In a preferred embodiment, the thicknesses of the foam absorption layer, the foam matching layer and the foam transition layer are in the range of 3-4 mm, 7-8 mm and 3-4 mm, respectively; the dielectric constants of the foam absorption layer, the foam matching layer and the foam transition layer are in the range of 30-35 F / m, 3-3.5 F / m and 12-14 F / m, respectively.
[0033] In a preferred embodiment, the honeycomb holes of the aramid paper honeycomb matrix are in the shape of a regular hexagon with a side length of 2 mm.
[0034] Another aspect of the present application provides a method for preparing the above-mentioned absorbing honeycomb material, comprising the following steps: 1) mixing the raw materials for forming the foam absorption layer, the foam matching layer and the optional foam transition layer to obtain the absorption layer rubber, the matching layer rubber and the optional transition layer rubber; 2) stacking the absorption layer rubber, the optional transition layer rubber and the matching layer rubber in sequence on an aramid paper honeycomb substrate; 3) performing heat preservation after each arrangement to obtain the foam absorption layer, the foam matching layer and the optional foam transition layer respectively.
[0035] The method for preparing absorbing honeycomb materials of the present invention is applied, and a gradient foaming design is performed in the honeycomb holes, that is, the dielectric constant of the foam matching layer is greater than the dielectric constant of the foam transition layer and the dielectric constant of the foam absorption layer, which can effectively expand the absorption bandwidth while reducing the thickness.
[0036] The technical route of the preparation method of the wave absorbing honeycomb material of the present invention is shown in Figure 1 .
[0037] In a preferred embodiment, the method for preparing an absorbing honeycomb material comprises the following steps: 1) mixing raw materials for forming a foam matching layer to obtain a matching layer rubber; 2) mixing raw materials for forming a foam absorption layer to obtain an absorption layer rubber; 3) optionally, mixing raw materials for forming a foam transition layer to obtain a transition layer rubber; 4) using a glue dispenser to inject the absorption layer rubber into the honeycomb holes of an aramid paper honeycomb substrate, and controlling the foaming height by controlling the amount of the injected rubber; 5) putting the material obtained in step 4) into an oven at 120-125°C for 40-50 minutes to obtain an absorbing honeycomb composite material filled with a foam absorption layer; 6) optionally, using a glue dispenser to inject the absorption layer rubber into the honeycomb holes of an aramid paper honeycomb substrate, and controlling the foaming height by controlling the amount of the injected rubber; 7) placing the material obtained in step 4) in an oven at 120-125°C for 40-50 minutes to obtain an absorbing honeycomb composite material filled with a foam absorption layer; 8) optionally, using a glue dispenser to inject the absorption layer rubber into the foam; 9) A transition layer of rubber is injected on the basis of the absorption layer, and the foaming height is controlled by controlling the amount of the injected rubber; 7) the material obtained in the optional step 6) is placed in an oven at 120-125°C for 40-50 minutes to obtain a foam transition layer-foam absorption layer filled absorbing honeycomb composite material; 8) a dispensing machine is used to inject a matching layer of rubber on the basis of the foam absorption layer or the optional foam transition layer, and the foaming height is controlled by controlling the amount of the injected rubber; 9) the material obtained in step 8) is placed in an oven at 120-125°C for 40-50 minutes to obtain a foam matching layer-optional foam transition layer-foam absorption layer filled absorbing honeycomb composite material.
[0038] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0039] The specifications of the raw materials used in the examples are as follows:
[0040] Expandable phenolic resin solid content ≥ 70%, Jining Huakai Resin Co., Ltd.
[0041] The average particle size of nano nickel powder is 60nm;
[0042] The curing agent is p-toluenesulfonic acid, purity ≥99.5%, Shandong Xinhui New Materials Co., Ltd.;
[0043] The foaming agent model is 180DU25, the average particle size is 20-30 microns, Shanghai Waidian International Trade Co., Ltd.;
[0044] The average particle size of hollow glass microspheres is 70 μm, and the bulk density is 0.29-0.35 g / cm 3 ;
[0045] The specific surface area of fumed silica is 380m 2 / g;
[0046] The resistivity of carbon black is 0.5-1.0Ω·cm, and the average particle size is 10-20 microns;
[0047] The specific surface area of graphene is 200m2 / g, tap density is 0.04g / cm 3 ;
[0048] The surfactant was Tween-10 or Tween-80, analytical grade, obtained from Sinopharm reagent;
[0049] The honeycomb cell side length of the aramid paper honeycomb matrix is 2 mm.
[0050] The wave-absorbing honeycomb material was prepared by the method described in the following examples:
[0051] Example 1
[0052] Step 1: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent, 20 parts of hollow glass microspheres, 5 parts of carbon black and 0.5 parts of fumed silica are mixed evenly by a disperser at 400-500 revolutions to obtain a matching layer rubber material; Step 2: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent and 20 parts of carbon black are mixed evenly to obtain an absorption layer rubber material; Step 3: Use a dispensing machine to inject the absorption layer rubber material into the honeycomb holes of an aramid paper honeycomb substrate with a size of 320*320*15mm, and control the foaming height by controlling the amount of injected rubber material. The dielectric constant is controlled between 30 and 33; Step 4: putting the material obtained in step 3 into an oven and keeping it warm at 120°C for 40-50 minutes to obtain an absorbing layer foam-filled absorbing honeycomb composite material; Step 5: using a dispensing machine to inject a matching layer of adhesive on the basis of the absorbing layer foam obtained in step 4, and controlling the foaming height to be 10-12mm by controlling the amount of injected adhesive, and controlling the dielectric constant to be between 3 and 3.3; Step 6: putting the material obtained in step 5 into an oven and keeping it warm at 120°C for 40-50 minutes to obtain a matching layer-absorbing layer foam-filled absorbing honeycomb composite material, and removing the overflowing part of the surface by grinding.
[0053] Example 2
[0054] The difference between Example 2 and Example 1 is that the type of the resistive absorber is changed.
[0055] Step 1: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent, 20 parts of hollow glass microspheres, 5 parts of carbon black and 0.5 parts of fumed silica are mixed evenly with a disperser at 400-500 revolutions to obtain a matching layer rubber material; Step 2: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent and 5 parts of graphene are mixed evenly to obtain an absorption layer rubber material; Step 3: Use a dispensing machine to inject the absorption layer rubber material into the honeycomb holes of an aramid paper honeycomb substrate with a size of 320*320*15mm, and control the foaming height by controlling the amount of injected rubber material. The dielectric constant is controlled between 33 and 35; Step 4: putting the material obtained in step 3 into an oven and keeping it warm at 120°C for 40-50 minutes to obtain an absorbing layer foam-filled absorbing honeycomb composite material; Step 5: using a dispensing machine to inject a matching layer of adhesive on the basis of the absorbing layer foam obtained in step 4, and controlling the foaming height to be 10-12mm by controlling the amount of injected adhesive, and controlling the dielectric constant to be between 3-3.3; Step 6: putting the material obtained in step 5 into an oven and keeping it warm at 120°C for 40-50 minutes to obtain a matching layer-absorbing layer foam-filled absorbing honeycomb composite material, and removing the overflowing part of the surface by grinding.
[0056] Example 3
[0057] The difference between Example 3 and Example 1 is that the type of the resistive absorber is changed.
[0058] Step 1: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent, 20 parts of hollow glass microspheres, 5 parts of carbon black and 0.5 parts of fumed silica are mixed evenly by a disperser at 400-500 revolutions to obtain a matching layer rubber material; Step 2: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent and 100 parts of nano nickel powder are mixed evenly to obtain an absorption layer rubber material; Step 3: Use a dispensing machine to inject the absorption layer rubber material into the honeycomb holes of an aramid paper honeycomb substrate with a size of 320*320*15mm, and control the foaming by controlling the amount of injected rubber material The height is 3-5mm, and the dielectric constant is controlled between 30-32; Step 4: Put the material obtained in step 3 into an oven and keep it warm at 120℃ for 40-50min to obtain an absorbing layer foam-filled absorbing honeycomb composite material; Step 5: Use a dispensing machine to inject a matching layer of glue on the basis of the absorbing layer foam obtained in step 4, and control the foaming height to 10-12mm by controlling the amount of injected glue, and control the dielectric constant to be between 3-3.3; Step 6: Put the material obtained in step 5 into an oven and keep it warm at 120℃ for 40-50min to obtain a matching layer-absorbing layer foam-filled absorbing honeycomb composite material, and remove the overflowed part of the surface by grinding.
[0059] Example 4
[0060] The difference between Example 4 and Example 1 is that a transition layer is introduced between the matching layer and the absorption layer.
[0061] Step 1: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent, 20 parts of hollow glass microspheres, 5 parts of carbon black and 0.5 parts of fumed silica are mixed uniformly by a disperser at 400-500 revolutions to obtain a matching layer rubber material; Step 2: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent and 20 parts of carbon black are mixed uniformly to obtain an absorption layer rubber material; Step Step 3: According to weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent and 5 parts of carbon black are mixed evenly to obtain transition layer glue; Step 4: Use a glue dispenser to inject the absorption layer glue into the honeycomb holes of the aramid paper honeycomb substrate with a size of 320*320*15mm, and control the foaming height to 3-5mm and the dielectric constant to 30-33 by controlling the amount of injected glue; Step 5: Mix the obtained in step 4 The material is put into an oven at 120°C for 40-50 minutes to obtain an absorbing layer foam-filled absorbing honeycomb composite material; Step six: injecting a transition layer of rubber material on the basis of the absorbing layer foam obtained in step five by using a dispensing machine, and controlling the foaming height to be 3-5mm and the dielectric constant to be between 12-13 by controlling the amount of injected rubber material; Step seven: putting the material obtained in step six into an oven at 120°C for 40-50 minutes to obtain a transition layer-absorbing layer foam-filled absorbing honeycomb composite material; Step eight: injecting a matching layer of rubber material on the basis of the transition layer foam obtained in step seven by using a dispensing machine, and controlling the foaming height to be 5-9mm and the dielectric constant to be between 3-3.3 by controlling the amount of injected rubber material; Step nine: putting the material obtained in step eight into an oven at 120°C for 40-50 minutes to obtain a matching layer-transition layer-absorbing layer foam-filled absorbing honeycomb composite material, and removing the surface overflow by grinding.
[0062] Example 5
[0063] The difference between Example 5 and Example 1 is that the raw material portions of the matching layer rubber material and the absorption layer rubber material are different.
[0064] Step 1: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent, 25 parts of hollow glass microspheres, 4 parts of carbon black and 0.5 parts of fumed silica are mixed evenly with a disperser at 400-500 revolutions to obtain a matching layer rubber material; Step 2: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent and 30 parts of carbon black are mixed evenly to obtain an absorption layer rubber material; Step 3: Use a dispensing machine to inject the absorption layer rubber material into the honeycomb holes of an aramid paper honeycomb substrate with a size of 320*320*15mm, and control the foaming height by controlling the amount of injected rubber material. The dielectric constant is controlled between 30-33 by controlling the height of the foam at 3-5mm; Step 4: putting the material obtained in step 3 into an oven and keeping it warm at 120°C for 40-50min to obtain an absorbing layer foam-filled absorbing honeycomb composite material; Step 5: injecting a matching layer of adhesive on the basis of the absorbing layer foam obtained in step 4 by using a dispensing machine, and controlling the foaming height to 10-12mm by controlling the amount of injected adhesive, and controlling the dielectric constant to be between 3-3.1; Step 6: putting the material obtained in step 5 into an oven and keeping it warm at 120°C for 40-50min to obtain a matching layer-absorbing layer foam-filled absorbing honeycomb composite material, and removing the overflowed part of the surface by grinding.
[0065] Example 6
[0066] The difference between Example 6 and Example 4 is that the raw material portions of the matching layer rubber material and the absorption layer rubber material are different.
[0067] Step 1: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent, 30 parts of hollow glass microspheres, 5 parts of carbon black and 0.5 parts of fumed silica are mixed uniformly by a disperser at 400-500 revolutions to obtain a matching layer rubber material; Step 2: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent and 25 parts of carbon black are mixed uniformly to obtain an absorption layer rubber material; Step Step 3: According to weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent and 4 parts of carbon black are mixed evenly to obtain transition layer glue; Step 4: Use a glue dispenser to inject the absorption layer glue into the honeycomb holes of the aramid paper honeycomb substrate with a size of 320*320*15mm, and control the foaming height to 3-5mm and the dielectric constant to 33-35 by controlling the amount of injected glue; Step 5: Mix the obtained in step 4 The material is put into an oven at 120°C for 40-50 minutes to obtain an absorbing layer foam-filled absorbing honeycomb composite material; Step six: inject a transition layer of rubber material on the basis of the absorbing layer foam obtained in step five using a dispensing machine, and control the foaming height to be 3-5mm by controlling the amount of injected rubber material. Control the dielectric constant to be between 12-13; Step seven: put the material obtained in step six into an oven at 120°C for 40-50 minutes to obtain a transition layer-absorbing layer foam-filled absorbing honeycomb composite material; Step eight: inject a matching layer of rubber material on the basis of the transition layer foam obtained in step seven using a dispensing machine, and control the foaming height to be 5-9mm by controlling the amount of injected rubber material, and control the dielectric constant to be between 3-3.2; Step nine: put the material obtained in step eight into an oven at 120°C for 40-50 minutes to obtain a matching layer-transition layer-absorbing layer foam-filled absorbing honeycomb composite material, and remove the surface overflow by grinding.
[0068] Comparative Example 1
[0069] The difference between Comparative Example 1 and Example 1 is that the matching layer is not provided.
[0070] Step 1: by weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent, 20 parts of carbon black and 0.5 parts of fumed silica are mixed evenly to obtain an absorption layer rubber material; Step 2: using a dispensing machine to inject the absorption layer rubber material into the honeycomb holes of an aramid paper honeycomb substrate with a size of 320*320*15mm, and by controlling the amount of the injected rubber material, the foaming height is controlled to be 15-17mm, and the dielectric constant is controlled to be between 30-33; Step 4: putting the material obtained in step 3 into an oven at 120°C for 40-50 minutes to obtain an absorption layer foam-filled wave-absorbing honeycomb composite material, and the overflowed part of the surface is removed by grinding.
[0071] Comparative Example 2
[0072] The difference between Comparative Example 2 and Example 2 is that Comparative Example 2 does not have a matching layer.
[0073] Step 1: by weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent, 5 parts of graphene and 0.5 parts of fumed silica are mixed evenly to obtain an absorption layer adhesive; Step 2: using a dispensing machine to inject the absorption layer adhesive into the honeycomb holes of an aramid paper honeycomb substrate with a size of 320*320*15mm, and by controlling the amount of the injected adhesive, the foaming height is controlled to be 15-17mm, and the dielectric constant is controlled to be between 33-35; Step 4: putting the material obtained in step 3 into an oven at 120°C for 40-50 minutes to obtain an absorption layer foam-filled wave-absorbing honeycomb composite material, and the overflowed part of the surface is removed by grinding.
[0074] Comparative Example 3
[0075] The difference between Comparative Example 3 and Example 3 is that Comparative Example 3 does not have a matching layer.
[0076] Step 1: by weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent, 100 parts of nano nickel powder and 0.5 parts of fumed silica are mixed evenly to obtain an absorption layer adhesive; Step 2: using a dispensing machine to inject the absorption layer adhesive into the honeycomb holes of an aramid paper honeycomb substrate with a size of 320*320*15mm, and by controlling the amount of the injected adhesive, the foaming height is controlled to be 15-17mm, and the dielectric constant is controlled to be between 30-32; Step 4: putting the material obtained in step 3 into an oven for 40-50 minutes at 120°C to obtain an absorption layer foam-filled wave-absorbing honeycomb composite material, and the overflowed part of the surface is removed by grinding.
[0077] Comparative Example 4
[0078] The difference between Comparative Example 4 and Example 1 is that no foaming is performed.
[0079] Step 1: By weight, 200 parts of expandable phenolic resin, 10 parts of curing agent, 20 parts of hollow glass microspheres, 5 parts of carbon black and 0.5 parts of fumed silica are mixed evenly with a disperser at 400-500 revolutions to obtain a matching layer rubber material; Step 2: By weight, 200 parts of expandable phenolic resin, 10 parts of curing agent and 20 parts of carbon black are mixed evenly to obtain an absorption layer rubber material; Step 3: Using a dispensing machine, the absorption layer rubber material is injected into the honeycomb holes of an aramid paper honeycomb substrate with a size of 320*320*15mm; Step 4: The material obtained in step 3 is placed in an oven at 120°C for 40-50 minutes; Step 5: Using a dispensing machine, the matching layer rubber material is injected on the basis of the absorption layer obtained in step 4; Step 6: The material obtained in step 5 is placed in an oven at 120°C for 40-50 minutes to obtain a wave-absorbing honeycomb composite material, and the overflowed part of the surface is removed by grinding.
[0080] Comparative Example 5
[0081] The difference between Comparative Example 5 and Example 1 is that the dielectric constant of the matching layer is greater than the dielectric constant of the absorption layer.
[0082] Step 1: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent, 20 parts of hollow glass microspheres, 30 parts of carbon black and 0.5 parts of fumed silica are mixed evenly with a disperser at 400-500 revolutions to obtain a matching layer rubber material; Step 2: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent and 20 parts of carbon black are mixed evenly to obtain an absorption layer rubber material; Step 3: Use a dispensing machine to inject the absorption layer rubber material into the honeycomb holes of an aramid paper honeycomb substrate with a size of 320*320*15mm, and control the foaming height by controlling the amount of injected rubber material. The dielectric constant is controlled between 30 and 31; Step 4: putting the material obtained in step 3 into an oven at 120°C for 40-50 minutes to obtain an absorbing layer foam-filled absorbing honeycomb composite material; Step 5: using a dispensing machine to inject a matching layer of adhesive on the basis of the absorbing layer foam obtained in step 4, and controlling the foaming height to be 10-12mm by controlling the amount of injected adhesive, and controlling the dielectric constant to be between 33 and 35; Step 6: putting the material obtained in step 5 into an oven at 120°C for 40-50 minutes to obtain a matching layer-absorbing layer foam-filled absorbing honeycomb composite material, and removing the overflowing part of the surface by grinding.
[0083] Comparative Example 6
[0084] The difference between Comparative Example 6 and Example 1 is that the thickness and dielectric constant of each layer are different.
[0085] Step 1: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent, 20 parts of hollow glass microspheres, 10 parts of carbon black and 0.5 parts of fumed silica are mixed evenly with a disperser at 400-500 revolutions to obtain a matching layer rubber material; Step 2: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent and 5 parts of carbon black are mixed evenly to obtain an absorption layer rubber material; Step 3: Use a dispensing machine to inject the absorption layer rubber material into the honeycomb holes of an aramid paper honeycomb substrate with a size of 320*320*15mm, and control the foaming height by controlling the amount of injected rubber material. The dielectric constant is controlled between 3 and 3.5; Step 4: putting the material obtained in step 3 into an oven at 120°C for 40-50 minutes to obtain an absorbing layer foam-filled absorbing honeycomb composite material; Step 5: using a dispensing machine to inject a matching layer of adhesive on the basis of the absorbing layer foam obtained in step 4, and controlling the foaming height to be 13-14mm by controlling the amount of injected adhesive, and controlling the dielectric constant to be between 30 and 33; Step 6: putting the material obtained in step 5 into an oven at 120°C for 40-50 minutes to obtain a matching layer-absorbing layer foam-filled absorbing honeycomb composite material, and removing the overflowing part of the surface by grinding.
[0086] Comparative Example 7
[0087] The difference between Comparative Example 7 and Example 1 is that the amount of raw materials in each layer is different.
[0088] Step 1: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent, 20 parts of hollow glass microspheres, 10 parts of carbon black and 0.5 parts of fumed silica are mixed evenly with a disperser at 400-500 revolutions to obtain a matching layer rubber material; Step 2: By weight, 200 parts of expandable phenolic resin, 8 parts of foaming agent, 4 parts of surfactant, 10 parts of curing agent and 5 parts of carbon black are mixed evenly to obtain an absorption layer rubber material; Step 3: Use a dispensing machine to inject the absorption layer rubber material into the honeycomb holes of an aramid paper honeycomb substrate with a size of 320*320*15mm, and control the foaming height by controlling the amount of injected rubber material At 3-5mm, the dielectric constant is controlled between 30-31; Step 4: Put the material obtained in step 3 into an oven and keep it warm at 120℃ for 40-50min to obtain an absorbing layer foam-filled absorbing honeycomb composite material; Step 5: Use a dispensing machine to inject a matching layer of glue on the basis of the absorbing layer foam obtained in step 4, and control the foaming height to 11-12mm by controlling the amount of injected glue, and control the dielectric constant to be between 3.3-3.5; Step 6: Put the material obtained in step 5 into an oven and keep it warm at 120℃ for 40-50min to obtain a matching layer-absorbing layer foam-filled absorbing honeycomb composite material, and remove the overflowed part of the surface by grinding.
[0089] The materials prepared in the embodiment and the comparative example were respectively taken and reflectivity tested in the range of 2 Hz to 18 GHz. The test results are shown in Table 1:
[0090] Table 1 Performance parameters of gradient filled microwave absorbing honeycomb foam
[0091]
[0092] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0093] By comparing Example 1 with Comparative Examples 1 and 4, Example 2 with Comparative Example 2, and Example 3 with Comparative Example 3, it can be seen that the absorbing honeycomb material having a foam absorbing layer and a foam matching layer of the present invention has improved electromagnetic wave absorption performance.
[0094] Comparison of Example 1 and Comparative Example 5 shows that the absorbing honeycomb material of the present invention, in which the dielectric constant of the foam matching layer is smaller than the dielectric constant of the foam absorbing layer, has improved electromagnetic wave absorption performance.
[0095] Comparison of Examples 1 and 5 with Comparative Examples 6 and 7 shows that the absorbing honeycomb material of the foam absorbing layer and the foam matching layer of the present invention having thickness, dielectric constant and raw material content within a specific range has improved electromagnetic wave absorption performance.
[0096] Comparing Example 1 with Example 4, it can be seen that the absorbing honeycomb material having the foam absorption layer, the foam transition layer and the foam matching layer of the present invention has further improved electromagnetic wave absorption performance.
[0097] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A microwave absorbing honeycomb material, characterized in that: The absorbing honeycomb material comprises an aramid paper honeycomb substrate and a foam absorption layer, an optional foam transition layer and a foam matching layer stacked in sequence from the inside to the outside on the aramid paper honeycomb substrate, wherein the dielectric constant of the foam matching layer is greater than the dielectric constant of the foam transition layer and is greater than the dielectric constant of the foam absorption layer.
2. The wave-absorbing honeycomb material according to claim 1, characterized in that: The raw materials for forming the foam absorption layer include a first expandable phenolic resin, a first foaming agent, a first surfactant, a first curing agent and a first resistive absorbent, wherein the first resistive absorbent includes carbon black, graphene or nano nickel powder; Preferably, the average particle size of the carbon black is 10 to 20 μm, and the resistivity is 0.5 to 1 Ω·cm; the specific surface area of the graphene is 1800 to 2000 m 2 / g, tap density is 0.08~0.1g / cm 3 The average particle size of the nano nickel powder is 50 to 70 nm.
3. The wave-absorbing honeycomb material according to claim 2, characterized in that: By weight, the raw materials for forming the foam absorption layer include 200-210 parts of the first expandable phenolic resin, 8-9 parts of the first foaming agent, 4-4.5 parts of the first surfactant, 10-11 parts of the first curing agent, and 20-30 parts of carbon black, 5-6 parts of graphene or 100-120 parts of nano nickel powder.
4. The microwave absorbing honeycomb material according to any one of claims 1 to 3, characterized in that: The raw materials for forming the foam matching layer include a second expandable phenolic resin, a second foaming agent, a second surfactant, a second curing agent, hollow glass microspheres and a second resistive absorber, wherein the second resistive absorber includes carbon black and fumed silica; Preferably, the average particle size of the hollow glass microspheres is 45-60 μm, and the bulk density is 0.29-0.35 g / cm 3 The average particle size of the carbon black is 10 to 20 μm, the resistivity is 0.5 to 1 Ω·cm, and the specific surface area of the fumed silica is 180 to 200 m 2 / g.
5. The wave-absorbing honeycomb material according to claim 4, characterized in that: By weight, the raw materials for forming the foam matching layer include 200-210 parts of the second expandable phenolic resin, 8-9 parts of the second foaming agent, 4-4.5 parts of the second surfactant, 10-11 parts of the second curing agent, 20-30 parts of hollow glass microspheres, 4-5 parts of carbon black and 0.5-0.7 parts of fumed silica.
6. The microwave absorbing honeycomb material according to any one of claims 1 to 3, characterized in that: The raw materials for forming the foam transition layer include a third expandable phenolic resin, a third foaming agent, a third surfactant, a third curing agent and carbon black; Preferably, the carbon black has an average particle size of 10 to 20 μm and a resistivity of 0.5 to 1 Ω·cm.
7. The wave-absorbing honeycomb material according to claim 6, characterized in that: By weight, the raw materials for forming the foam transition layer include 200-210 parts of the third expandable phenolic resin, 8-9 parts of the third foaming agent, 4-4.5 parts of the third surfactant, 10-11 parts of the third curing agent and 4-5 parts of carbon black.
8. The wave-absorbing honeycomb material according to claim 1, characterized in that: The thicknesses of the foam absorption layer, the foam matching layer and the foam transition layer are in the range of 3-4 mm, 6-7 mm and 3-4 mm respectively; The dielectric constants of the foam absorbent layer, the foam matching layer and the foam transition layer are in the range of 30-35 F / m, 3-3.5 F / m and 12-14 F / m, respectively.
9. The wave-absorbing honeycomb material according to claim 1, characterized in that: The honeycomb holes of the aramid paper honeycomb matrix have a regular hexagonal shape with a side length of 2.0 mm.
10. A method for preparing the wave-absorbing honeycomb material according to any one of claims 1 to 9, the method comprising the following steps: 1) mixing raw materials for forming the foam absorbent layer, the foam matching layer and the optional foam transition layer to obtain an absorbent layer rubber material, a matching layer rubber material and an optional transition layer rubber material; 2) stacking the absorption layer rubber, the optional transition layer rubber and the matching layer rubber in sequence on the aramid paper honeycomb substrate; 3) After each arrangement, heat preservation is performed to obtain the foam absorption layer, the foam matching layer and the optional foam transition layer respectively.
Citation Information
Patent Citations
Foam-filled aramid paper honeycomb wave-absorbing structure and preparation method thereof
CN113211883A
Wave-absorbing honeycomb with aramid paper surface layer coated with absorbent and preparation method of wave-absorbing honeycomb
CN115821642A
Wave-absorbing honeycomb with impedance matching structure and preparation method thereof
CN115891293A
Wave-absorbing honeycomb with pyramid-shaped electric structure and preparation method of wave-absorbing honeycomb
CN115946425A
space absorber for electromagnetic waves made of material of high mechanical resistance
FR1514480A